Konstytucja rocznicowa czy konstytucja wiekopomna? - Pospieszalski, Karol Marian; Ziembiński, Zygmunt (Wydział Prawa i Administracji UAM, 1991)
The article addresses the central issue of works conducted at present on the new Constitution of the Republic of Poland. In particular, it lists arguments speaking for the acceleration of these works and the adoption of the new Constitution in time for the 200th Anniversary of the first Constitution in Europe, the Polish Constitution of 1791, and the arguments speaking for the retention of Constitutional provisorium resulting from the Constitution of 1952, the retention of which would make it possible to draft the Constitution in the way that could reflect a stabilized situation in post-communist Poland and could provide precise and accurate legal solutions, with good prospects for securing the stability of the Polish Constitutional order.
The anniversary constitution or the memorable constitution?